Cast bionic metal ceramic plough share and manufacturing method thereof
By synthesizing the metal cermet layer in situ on the working surface of the plowshare casting, and using combustion synthesis reaction to generate TiC and Al2O3 particles, combined with hard particles such as nickel-based WC, the problem of insufficient wear resistance and service life of the plowshare in the prior art is solved, and the problem of insufficient wear resistance and service life of the plowshare in the prior art is realized. Improves high wear resistance and desorption and viscosity reduction effects.
Patent Information
- Application Number
- CN202411276876.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The existing plowshare production process cannot meet the needs of high wear resistance and high service life. The surfacing and cladding technology has problems such as high cost, low bonding strength, and poor desorption and viscosity reduction.
By casting bionic cermet plowshares, the cermet layer is synthesized in situ on the working surface of the plowshare casting, the scale structure is designed, and the combustion synthetic alloy powder is mixed with water-based binder, and the high-temperature metal melt initiates the combustion synthesis reaction to generate TiC and Al2O3 particles and have physical and chemical reactions with alloy powders such as nickel-based WC to form a composite plowshare and are heat treated to improve wear resistance and desorption and viscosity reduction properties.
Achieve high wear resistance and long service life composite plowshare, simplify production process, reduce costs, significantly improve the wear resistance and desorption reduction effect of plowshare, and solve the service life caused by poor wear resistance in traditional technology. Short question.
Smart Images

Figure CN119114857A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wear-resistant composite materials, and in particular to a casting bionic metal ceramic ploughshare and a preparation method thereof. Background Art
[0002] The plowshare is a typical soil-contacting part and an important consumable part of the reversible plow. Its wear resistance directly affects the tillage efficiency and service life of the reversible plow. Whether the reversible plowshare is processed by surfacing, laser cladding, vacuum cladding and other technologies to improve its wear resistance, secondary processing is required on the plowshare.
[0003] The existing surfacing technology and cladding technology are both secondary processing on the plowshare body, which has the key problems of high cost of cladding materials, inability to effectively carry out actual large-scale production, low bonding strength between the surface strengthening layer and the substrate, and poor desorption and viscosity reduction effect on rock and soil during use, making it difficult to meet the requirements of high wear resistance and high service life of the plowshare as a whole. Summary of the invention
[0004] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a cast bionic metal ceramic plowshare and a method for manufacturing the same. In view of the problem that the existing plowshare production process cannot meet the requirements of high wear resistance and high service life, the present invention provides a method for manufacturing a composite material plowshare with high wear resistance and high service life and having desorption and viscosity reduction effects. The method uses a metal ceramic layer synthesized in situ on the working surface of the plowshare casting to form the metal ceramic layer in one casting process without the need for secondary processing, and the process is simple, fast and efficient.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A method for manufacturing a cast bionic metal ceramic ploughshare comprises the following steps:
[0007] A scale structure is designed at the position where the ploughshare touches the soil, and a ploughshare coated sand shell model with the scale structure is made.
[0008] The water-based binder and the combustion synthesized alloy powder are kneaded to form an alloy powder paste, and the alloy powder paste is coated on the scale structure in the sand shell model of the plowshare coated sand and dried, wherein the alloy powder contains aluminum powder, titanium powder, chromium powder, Cr 2 O 3 Powder, NiO powder, graphite powder and nickel-based tungsten carbide powder.
[0009] The dried ploughshare coated sand shell model is assembled with the pouring system and filled with quartz sand. The low alloy structural steel liquid is melted by the casting system to obtain the molten metal. The molten metal is then poured into the cavity of the ploughshare coated sand shell model. The high temperature molten metal triggers a combustion synthesis reaction, and TiC and Al are generated in situ on the scale structure. 2 O 3 Particles and release a lot of heat. At the same time, the high-temperature molten steel penetrates into the alloy particle layer, and physical and chemical reactions occur between the nickel-based WC and other alloy powder particles in the alloy powder to obtain a composite plowshare casting.
[0010] The composite plowshare casting is heat treated to obtain a cast bionic metal ceramic plowshare. The heat treatment operation can eliminate the casting stress of the hard metal ceramic coating, refine the structure, make the composition more uniform, and improve the particle morphology; on the other hand, it can also improve the comprehensive mechanical properties of the matrix, ensuring the protection of the hard particles.
[0011] The present invention designs a scale structure at the part where the plowshare touches the soil, and manufactures a plowshare coated sand shell model with a scale structure. The scale structure on the surface of the plowshare tip has non-smooth protrusions and ridges. These protrusions and ridges will first contact the soil during work, reducing the contact area with the soil, and the gullies between the protrusions and ridges will also serve as a transportation channel for the turned soil, achieving desorption, viscosity reduction and drag reduction. The schematic diagram of the composite plowshare prepared by the present invention is as follows Figure 7 As shown, 1 is the plowshare substrate, 2 is the bionic structure metal ceramic coating, Figure 8 for Figure 7 The enlarged image of the two bionic structures in the middle. Then, a water-based binder and a combustion-synthesized alloy powder are prepared into an alloy powder paste and coated on the soil-touching part of the ploughshare coated sand shell model. The ploughshare coated sand shell model is assembled with a casting system. The low-alloy structural steel liquid is melted by the casting system to obtain a metal melt. The metal melt is then poured into the cavity of the ploughshare coated sand shell model. The self-propagating high-temperature synthesis method is suitable for preparing high-temperature refractory inorganic non-metallic materials. The self-heating and self-conduction effect of the high chemical reaction heat between the reactant powders is used to synthesize new materials. The high-temperature metal melt triggers a combustion synthesis reaction to generate TiC and Al in situ. 2 O 3 particles and release a large amount of heat. At the same time, the high-temperature molten steel penetrates into the alloy particle layer, and physically and chemically reacts with the nickel-based WC and other alloy powder particles in the alloy powder to obtain a composite ploughshare casting. Finally, the composite ploughshare casting is heat treated to obtain a cast bionic metal ceramic ploughshare.
[0012] In a preferred embodiment of the present invention, the alloy powder comprises 10wt% to 20wt% aluminum powder, 20wt% to 40wt% titanium powder, 5wt% to 20wt% chromium powder, and Cr2 O 3 5wt% to 10wt% of aluminum powder, 10wt% to 20wt% of NiO powder, 10wt% to 20wt% of graphite powder, and 5wt% to 20wt% of nickel-based tungsten carbide particles; wherein the particle size of aluminum powder is 5μm to 40μm, the particle size of titanium powder is 18μm to 150μm, the particle size of chromium powder is 20μm to 150μm, and the particle size of Cr 2 O 3 The powder particle size is 2μm to 25μm, the NiO powder particle size is 2μm to 25μm, the graphite powder particle size is 1.3μm to 20μm, and the nickel-based tungsten carbide particle size is 20μm to 200μm.
[0013] In a preferred embodiment of the present invention, the water-based adhesive is one of a gum arabic aqueous solution, a potato starch adhesive aqueous solution, and an ethylene-vinyl acetate copolymer emulsion adhesive.
[0014] In a preferred embodiment of the present invention, in the alloy powder paste, the volume fraction of the binder is 10% to 30%, the mass concentration of the gum arabic aqueous solution is 1% to 10%, the mass concentration of the potato starch binder aqueous solution is 1% to 8%, and the mass concentration of the ethylene-vinyl acetate copolymer emulsion adhesive is 5% to 15%.
[0015] In a preferred embodiment of the present invention, the low alloy structural steel is one of ZG20CrNiMoRE, ZG25CrNiMoRE, and ZG30CrNiMoRE, wherein the carbon content of ZG20CrNiMoRE structural steel is 0.18% to 0.22%, the carbon content of ZG25CrNiMoRE structural steel is 0.22 to 0.28, and the carbon content of ZG30CrNiMoRE structural steel is 0.28 to 0.32.
[0016] In a preferred embodiment of the present invention, the coating thickness of the alloy powder paste is 4 mm to 10 mm.
[0017] In a preferred embodiment of the present invention, the pouring temperature is 1570°C to 1620°C.
[0018] In a preferred embodiment of the present invention, the heat treatment operation is: first keep the temperature at 930°C to 980°C for 2 to 6 hours, cool to room temperature, and then keep the temperature at 280°C to 340°C for 1 to 4 hours for tempering.
[0019] Another object of the present invention is to provide a cast bionic metal ceramic ploughshare produced by any of the preparation methods described above, wherein the cast bionic metal ceramic ploughshare consists of a ploughshare substrate and a hard metal ceramic coating at the soil-contacting portion.
[0020] In a preferred embodiment of the present invention, the plowshare base material is low alloy high strength structural steel, the base material impact energy is 50J-100J, the base hardness is 46HRC-52HRC, and the Rockwell hardness of the hard metal ceramic coating is 60HRC-69HRC.
[0021] In a preferred embodiment of the present invention, the hard metal ceramic alloy layer is composed of in-situ generated TiC, Al 2 O 3 The ceramic particles and the added nickel-based WC particles are organically integrated with the matrix alloy bonding phase, in which the matrix alloy bonding phase has Cr precipitated from the matrix phase in addition to the ferrite matrix. 7 C 3、 (Ti,W)C and other carbides.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention mixes the combustion synthesis alloy powder with a water-based binder to prepare an alloy powder paste, and applies the alloy powder paste to the soil-contacting part of the ploughshare coated sand shell model with a scale structure, then assembles the model with a casting system, melts the structural steel liquid, and the high-temperature metal melt triggers a combustion synthesis reaction to generate TiC and Al in situ. 2 O 3 The particles are formed and a large amount of heat is released. At the same time, the high-temperature molten steel penetrates into the alloy particle layer and reacts physically and chemically with the added nickel-based WC and other alloy powder particles. Then, the composite ploughshare casting is cast and heat-treated to obtain a cast bionic metal ceramic ploughshare. The combustion synthesis hard particle technology is combined with the casting infiltration process to generate TiC and Al in situ through the combustion synthesis reaction. 2 O 3 The particles are melted and a certain amount of heat is released. The nickel-based tungsten carbide powder in the alloy powder partially melts and wraps part of the TiC particles generated by the reaction to form (Ti, W) C complex phase hard particles with a core-shell structure. At the same time, the melted Ni element improves the wettability of the (Ti, W) C complex phase hard particles, nickel-based tungsten carbide and the matrix, and improves the overall wear resistance of the plowshare. The present invention is provided with a reinforcement for increasing the wear resistance of the plowshare tip at the plowshare shovel tip. The reinforcement is a metal-ceramic composite material. By providing a bionic flaky reinforcement on the wear-resistant working surface of the plowshare shovel tip, the wear resistance of the composite plowshare shovel tip is further improved. At the same time, the special bionic drag reduction structure in the present invention can significantly improve the desorption and viscosity reduction effect during the contact between the plowshare and the soil, further improve the tillage efficiency of the plowshare, and can well solve the problem of short service life of the flip plowshare produced by traditional technology due to poor wear resistance.
[0024] 2. The composite plowshare of the present invention has a simple production process, and the metal-ceramic alloy hardening layer is cast simultaneously with the plowshare casting, which greatly shortens the production process of the composite plowshare, has low manufacturing cost, and is easy to industrialize. A non-smooth pangolin scale bionic structure is formed on the surface of the plowshare, which greatly improves the wear resistance and desorption, viscosity reduction and drag reduction performance of the plowshare, thereby extending the service life, improving farming efficiency, and reducing farming costs.
[0025] 3. Cr added to the combustion synthesized alloy powder of the present invention 2 O 3 , NiO oxide powder reacts with aluminum powder to generate Al 2 O 3 The particles are formed and a large amount of heat is released. The reaction can also reduce metal elements such as Cr and Ni and melt into the matrix phase together with the added metal chromium powder, producing a solid solution strengthening effect, which greatly improves the strength of the matrix phase; the metal chromium and the carbon element in the matrix phase form fine chromium carbides, which can refine the grain size of the matrix phase and play a role in fine grain strengthening and dispersion strengthening. The combined effect of the three strengthening mechanisms greatly improves the protective effect of the matrix on the hard ceramic particles. The addition of RE rare earth to the matrix molten steel improves the quality of the molten steel, improves the fluidity of the molten steel, and further improves the wettability of the matrix molten steel and ceramic particles.
[0026] 4. In-situ generation of TiC and Al 2 O 3 The wear-resistant area of the ploughshare tip is reinforced with dispersed ceramic particles and external nickel-based WC and other hard particles; the impact energy value of the ploughshare matrix material ranges from 50J to 100J, and the hardness value of the metal-ceramic alloy hardened layer ranges from 60HRC to 69HRC, which ensures that the composite ploughshare has high toughness and improves the hardness and wear resistance of the wear service part of the ploughshare tip; TiC and Al generated in situ by combustion synthesis reaction are used to 2 O 3 The microhardness of the added WC particles is significantly higher than that of the chromium carbides in the cladding material that play an anti-wear role. The volume fraction of the hard ceramic particles is between 40% and 60%. The hardened layer of the metal-ceramic alloy has a dense structure, which makes it have excellent wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a microstructure photograph of the interface between the composite matrix and the metal-ceramic coating.
[0028] Figure 2 This is a microstructure photograph of the metal-ceramic coating at the interface of the composite material.
[0029] Figure 3 This is a photo of the matrix and endogenous TiC particle structure at the interface of the composite material.
[0030] Figure 4 Photo of the internal structure of the composite metal-ceramic coating.
[0031] Figure 5 for Figure 4 Magnified 3000 times tissue photo.
[0032] Figure 6 These are the wear test results of the metal ceramic ploughshare material prepared by the present invention.
[0033] Figure 7 This is a schematic diagram of a composite ploughshare prepared by the method of the present invention, wherein: 1-ploughshare substrate; 2-metal ceramic coating at the soil contacting portion.
[0034] Figure 8 for Figure 7 Enlarged view of the two bionic structures in the middle. DETAILED DESCRIPTION
[0035] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0037] The present invention is a method for manufacturing a composite material plowshare that overcomes the problem that the existing plowshare production process cannot meet the requirements of high wear resistance and long service life. First, according to the actual wear condition of the plowshare, a plowshare casting shape with a pangolin-like scale structure is designed at the part that needs wear resistance, and then a coated sand casting mold is made. The coated sand material is injected into the heated mold under a certain pressure, and the plowshare coated sand shell is obtained after cooling and solidification. Combustion-synthesized metal ceramic powder is coated in the groove with the scale structure, and then dried. The dried composite plowshare coated sand shell model and the casting system are assembled into a box and filled with 20-40 mesh dry quartz sand. Low-alloy high-strength structural steel liquid is smelted, and the high-temperature metal melt triggers a combustion synthesis reaction to generate TiC and Al in situ. 2 O 3The particles are formed and a large amount of heat is released. At the same time, the high-temperature molten steel penetrates into the alloy particle layer, and physical and chemical reactions occur between the added nickel-based WC and other alloy powder particles. After cooling and cleaning, and then heat treatment, a high-toughness, high-hardness, and wear-resistant metal-ceramic composite plowshare can be manufactured. The plowshare matrix is made of low-alloy high-strength structural steel. The plowshare liquid molding process uses the coated sand casting process. The thickness of the hard metal ceramic coating generated on the surface of the plowshare matrix is 4mm to 10mm. The hard metal ceramic alloy layer is mainly composed of in-situ generated TiC and Al 2 O 3 And nickel-based WC particles and a small amount of M 7 C 3 It is composed of carbide and matrix alloy bonding phase, with hardness HRC60-69. The hard metal ceramic coating composite plowshare has good impact resistance and wear resistance during use, and the wear-resistant cemented carbide layer does not fall off during service.
[0038] Example 1
[0039] A method for manufacturing a cast bionic metal ceramic ploughshare comprises the following steps:
[0040] (1) According to the actual wear condition of the plowshare, a plowshare casting shape with a pangolin scale structure is designed at the part that needs wear resistance, and then a coated sand model with a composite plow tip with a scale structure is made. The coated sand is injected into a heated mold under a pressure of 0.5 MPa. After cooling and solidification, a plowshare coated sand shell model with a scale structure is obtained.
[0041] (2) A combustion synthesized alloy powder is prepared into a paste using a potato starch binder having a mass concentration of 5%, wherein the volume fraction of the binder is 20%, wherein the combustion synthesized alloy powder includes aluminum powder having a particle size of 5 μm to 40 μm and 15 wt %, titanium powder having a particle size of 18 μm to 150 μm and 30 wt %, chromium powder having a particle size of 20 μm to 150 μm and 10 wt %, Cr powder having a particle size of 2 μm to 25 μm and 8 wt %. 2 O 3 Powder, particle size 2μm~25μm, 15wt% NiO powder, particle size 1.3μm~20μm, 17wt% graphite powder, particle size 20μm~200μm, 5wt% nickel-based tungsten carbide particles, the alloy powder paste is evenly coated on the internal working surface of the coated sand shell model, the coating thickness is 6mm, and the coated sand mold is dried.
[0042] (3) The dried composite plow tip coated sand shell model is assembled with the pouring system and filled with 30 mesh dry quartz sand. According to the national standard GB / T40802-2021 for wear-resistant steel castings, ZG30CrNiMoRE low-alloy high-strength structural steel liquid is smelted to obtain a molten metal. The molten metal is then poured into the cavity of the plowshare coated sand shell model. The high-temperature molten metal triggers a combustion synthesis reaction to generate TiC and Al in situ. 2 O 3 Particles and release a lot of heat. At the same time, high-temperature molten steel penetrates into the alloy particle layer, and physical and chemical reactions occur between the added nickel-based WC and other alloy powder particles. The pouring temperature is 1580℃. After the pouring is completed, it is left to stand for 2 hours, then the box is turned over, the sand is removed, and the composite plowshare casting is obtained after cleaning and grinding.
[0043] (4) The composite ploughshare casting is heated to 960° C. and kept at this temperature for 4 hours, rapidly cooled in water, cooled to room temperature, and then kept at 290° C. for 2 hours for tempering to obtain a cast bionic metal ceramic ploughshare.
[0044] Example 2
[0045] A method for manufacturing a cast bionic metal ceramic ploughshare comprises the following steps:
[0046] (1) According to the actual wear condition of the plowshare, a plowshare casting shape with a pangolin scale structure is designed at the part that needs wear resistance, and then a coated sand model with a composite plow tip with a scale structure is made. The coated sand is injected into a heated mold under a pressure of 0.6 MPa. After cooling and solidification, a plowshare coated sand shell model with a scale structure is obtained.
[0047] (2) A combustion synthesized alloy powder is prepared into a paste using a potato starch binder having a mass concentration of 5%, wherein the volume fraction of the binder is 20%, wherein the combustion synthesized alloy powder includes aluminum powder having a particle size of 5 μm to 40 μm and 15 wt %, titanium powder having a particle size of 18 μm to 150 μm and 30 wt %, chromium powder having a particle size of 20 μm to 150 μm and 10 wt %, Cr powder having a particle size of 2 μm to 25 μm and 8 wt %. 2 O 3 Powder, particle size 2μm~25μm, 15wt% NiO powder, particle size 1.3μm~20μm, 15wt% graphite powder, particle size 20μm~200μm, 7wt% nickel-based tungsten carbide particles, the alloy powder paste is evenly coated on the internal working surface of the coated sand shell model, the coating thickness is 7mm, and the coated sand mold is dried.
[0048] (3) The dried composite plow tip coated sand shell model and the pouring system are assembled together and filled with 20 mesh dry quartz sand. According to the national standard GB / T40802-2021 for wear-resistant steel castings, ZG25CrNiMoRE low-alloy high-strength structural steel liquid is smelted to obtain a molten metal. The molten metal is then poured into the cavity of the plowshare coated sand shell model. The high-temperature molten metal triggers a combustion synthesis reaction to generate TiC and Al in situ. 2 O 3 Particles and release a lot of heat. At the same time, high-temperature molten steel penetrates into the alloy particle layer, and physical and chemical reactions occur between the added nickel-based WC and other alloy powder particles. The pouring temperature is 1600℃. After the pouring is completed, it is left to stand for 2 hours, then the box is turned over, the sand is removed, and the composite plowshare casting is obtained after cleaning and grinding.
[0049] (3) The composite ploughshare casting is heated to 980° C. and kept at this temperature for 4 hours, rapidly cooled in water, cooled to room temperature, and then tempered at 300° C. for 2 hours to obtain a cast bionic metal ceramic ploughshare.
[0050] Example 3
[0051] A method for manufacturing a cast bionic metal ceramic ploughshare comprises the following steps:
[0052] (1) According to the actual wear condition of the plowshare, a plowshare casting shape with a pangolin scale structure is designed at the part that needs wear resistance, and then a coated sand model with a composite plow tip with a scale structure is made. The coated sand is injected into a heated mold under a pressure of 0.5 MPa. After cooling and solidification, a plowshare coated sand shell model with a scale structure is obtained.
[0053] (2) A combustion synthesized alloy powder is prepared into a paste using a potato starch binder having a mass concentration of 5%, wherein the volume fraction of the binder is 20%, wherein the combustion synthesized alloy powder includes aluminum powder having a particle size of 5 μm to 40 μm and 15 wt %, titanium powder having a particle size of 18 μm to 150 μm and 30 wt %, chromium powder having a particle size of 20 μm to 150 μm and 10 wt %, Cr powder having a particle size of 2 μm to 25 μm and 8 wt %. 2 O 3 Powder, particle size 2-25μm, 15wt% NiO powder, particle size 1.3μm-20μm, 15wt% graphite powder, particle size 20μm-200μm, 7wt% nickel-based tungsten carbide particles, the alloy powder paste is evenly coated on the inner working surface of the coated sand shell model, the coating thickness is 10mm, and the coated sand mold is dried.
[0054] (3) The dried composite plow tip coated sand shell model and the pouring system are assembled together and filled with 40 mesh dry quartz sand. According to the national standard GB / T40802-2021 for wear-resistant steel castings, ZG20CrNiMoRE low-alloy high-strength structural steel liquid is smelted to obtain a molten metal. The molten metal is then poured into the cavity of the plowshare coated sand shell model. The high-temperature molten metal triggers a combustion synthesis reaction to generate TiC and Al in situ. 2 O 3 Particles and release a lot of heat. At the same time, high-temperature molten steel penetrates into the alloy particle layer, and physical and chemical reactions occur between the added nickel-based WC and other alloy powder particles. The pouring temperature is 1620℃. After the pouring is completed, it is left to stand for 2 hours, then the box is turned over, the sand is removed, and the composite plowshare casting is obtained after cleaning and grinding.
[0055] (3) The composite ploughshare casting is heated to 980° C. and kept at this temperature for 4 hours, rapidly cooled in water, cooled to room temperature, and then tempered at 340° C. for 4 hours to obtain a cast bionic metal ceramic ploughshare.
[0056] Example 4
[0057] A method for manufacturing a cast bionic metal ceramic ploughshare comprises the following steps:
[0058] (1) According to the actual wear condition of the plowshare, a plowshare casting shape with a pangolin scale structure is designed at the part that needs wear resistance, and then a coated sand model with a composite plow tip with a scale structure is made. The coated sand is injected into a heated mold under a pressure of 0.5 MPa. After cooling and solidification, a plowshare coated sand shell model with a scale structure is obtained.
[0059] (2) A combustion synthesized alloy powder is prepared into a paste using a potato starch binder having a mass concentration of 5%, wherein the volume fraction of the binder is 10%, wherein the combustion synthesized alloy powder includes aluminum powder having a particle size of 5 μm to 40 μm and 10 wt %, titanium powder having a particle size of 18 μm to 150 μm and 40 wt %, chromium powder having a particle size of 20 μm to 150 μm and 5 wt %, Cr powder having a particle size of 2 μm to 25 μm and 5 wt %. 2 O 3 Powder, particle size 2μm~25μm, 20wt% NiO powder, particle size 1.3μm~20μm, 10wt% graphite powder, particle size 20μm~200μm, 10wt% nickel-based tungsten carbide particles, the alloy powder paste is evenly coated on the internal working surface of the coated sand shell model, the coating thickness is 6mm, and the coated sand mold is dried.
[0060] (3) The dried composite plow tip coated sand shell model is assembled with the pouring system and filled with 30 mesh dry quartz sand. According to the national standard GB / T40802-2021 for wear-resistant steel castings, ZG30CrNiMoRE low-alloy high-strength structural steel liquid is smelted to obtain a molten metal. The molten metal is then poured into the cavity of the plowshare coated sand shell model. The high-temperature molten metal triggers a combustion synthesis reaction to generate TiC and Al in situ. 2 O 3 Particles and release a lot of heat. At the same time, high-temperature molten steel penetrates into the alloy particle layer, and physical and chemical reactions occur between the added nickel-based WC and other alloy powder particles. The pouring temperature is 1570℃. After the pouring is completed, it is left to stand for 2 hours, then the box is turned over, the sand is removed, and the composite plowshare casting is obtained after cleaning and grinding.
[0061] (4) The composite ploughshare casting is heated to 930° C. and kept at this temperature for 6 hours, rapidly cooled in water, cooled to room temperature, and then tempered at 280° C. for 4 hours to obtain a cast bionic metal ceramic ploughshare.
[0062] Example 5
[0063] A method for manufacturing a cast bionic metal ceramic ploughshare comprises the following steps:
[0064] (1) According to the actual wear condition of the plowshare, a plowshare casting shape with a pangolin scale structure is designed at the part that needs wear resistance, and then a coated sand model with a composite plow tip with a scale structure is made. The coated sand is injected into a heated mold under a pressure of 0.5 MPa. After cooling and solidification, a plowshare coated sand shell model with a scale structure is obtained.
[0065] (2) A combustion synthesized alloy powder is prepared into a paste using a potato starch binder having a mass concentration of 5%, wherein the volume fraction of the binder is 30%, wherein the combustion synthesized alloy powder includes aluminum powder having a particle size of 5 μm to 40 μm and 20 wt%, titanium powder having a particle size of 18 μm to 150 μm and 20 wt%, chromium powder having a particle size of 20 μm to 150 μm and 20 wt%, Cr powder having a particle size of 2 μm to 25 μm and 10 wt%. 2 O 3 Powder, particle size 2μm~25μm, 10wt% NiO powder, particle size 1.3μm~20μm, 10wt% graphite powder, particle size 20μm~200μm, 10wt% nickel-based tungsten carbide particles, the alloy powder paste is evenly coated on the internal working surface of the coated sand shell model, the coating thickness is 4mm, and the coated sand mold is dried.
[0066] (3) The dried composite plow tip coated sand shell model is assembled with the pouring system and filled with 30 mesh dry quartz sand. According to the national standard GB / T40802-2021 for wear-resistant steel castings, ZG30CrNiMoRE low-alloy high-strength structural steel liquid is smelted to obtain a molten metal. The molten metal is then poured into the cavity of the plowshare coated sand shell model. The high-temperature molten metal triggers a combustion synthesis reaction to generate TiC and Al in situ. 2 O 3 Particles and release a lot of heat. At the same time, high-temperature molten steel penetrates into the alloy particle layer, and physical and chemical reactions occur between the added nickel-based WC and other alloy powder particles. The pouring temperature is 1620℃. After the pouring is completed, it is left to stand for 2 hours, then the box is turned over, the sand is removed, and the composite plowshare casting is obtained after cleaning and grinding.
[0067] (4) The composite ploughshare casting is heated to 980° C. and kept at this temperature for 2 hours, rapidly cooled in water, cooled to room temperature, and then kept at 340° C. for 1 hour for tempering to obtain a cast bionic metal ceramic ploughshare.
[0068] Results Analysis
[0069] The coated sand casting process is used to form a wear-resistant metal ceramic alloy hardened layer with a thickness of 4 to 10 mm on the working surface of the ploughshare shovel tip; the composite ploughshare substrate and the wear-resistant metal ceramic carbide layer are metallurgically bonded, and the wear-resistant metal ceramic alloy hardened layer is mainly composed of TiC generated in situ by combustion synthesis reaction and added WC, Al 2 O 3 Equal particles and a small amount of M 7 C 3 It is composed of type carbide, the impact energy of the plowshare matrix is 50J-65J, and the Rockwell hardness is HRC65-69.
[0070] Figure 1 The photo shows the microstructure of the interface between the composite material matrix and the metal ceramic coating of the present invention. The lower right part of the picture shows the low alloy steel microstructure of the matrix, which is mainly composed of low carbon lath martensite; the upper left part shows the metal ceramic microstructure, which is mainly composed of TiC, Al 2 O 3 It is composed of ceramic particle phase and steel-based metal matrix phase. The interface between the two phases is not obvious, and the two phases are metallurgically bonded.
[0071] Figure 2 This is a photograph of the metal-ceramic coating structure at the interface of the composite material of the present invention. The structure shown in the figure is the structure on the side of the metal-ceramic coating at the interface of the composite material. It can be seen that the metal-ceramic structure is uniform and dense, with very few pores and slag inclusion defects.
[0072] Figure 3This is a microstructure photograph of the matrix and endogenous TiC particles at the interface of the composite material of the present invention. The microstructure shown in the figure is the microstructure on the matrix side close to the interface of the composite material. It can be seen that the in-situ synthesized black TiC fine particles are dispersed on the low-carbon martensite structure of the matrix.
[0073] Figure 4 This is a photo of the internal structure of the composite metal ceramic coating of the present invention. Figure 5 for Figure 4 The organizational photograph is magnified 3000 times. It can be seen from the figure that the black part is endogenous TiC particles, the surrounding gray part is mainly nickel and tungsten elements, and the white particles are nickel-based WC particles.
[0074] Figure 6 The wear test results of the metal ceramic ploughshare material prepared by the present invention, wherein T0 is the surfacing material, and T1-T5 are the weight loss results of metal ceramic coating materials with different proportions and thicknesses. Among them, T1 is the metal ceramic coating material prepared in Example 1, T2 is the metal ceramic coating material prepared by replacing the nickel-based WC addition in Example 1 with 10%, T3 is the metal ceramic coating material prepared by replacing the nickel-based WC addition in Example 1 with 15%, T4 is the metal ceramic coating material prepared by replacing the nickel-based WC addition in Example 1 with 20%, T5 is the metal ceramic coating material prepared by replacing the nickel-based WC addition in Example 1 with 25%, and Figure 6 It can be seen that after adding nickel-based WC particles, the wear resistance of the composite ploughshare hardened layer is higher than that of traditional surfacing materials under three different loads; among them, when the addition amount of nickel-based WC is 15%, its wear resistance is the best.
[0075] In summary, the present invention combines the combustion synthesis hard particle technology with the casting infiltration process, and uses the combustion synthesis reaction to generate TiC and Al in situ. 2 O 3 The wear-resistant area of the ploughshare tip is reinforced with dispersed ceramic particles and external nickel-based WC and other hard particles; the impact energy value of the ploughshare matrix material ranges from 50J to 100J, and the hardness value of the metal-ceramic alloy hardened layer ranges from 60 to 69HRC, which ensures that the composite ploughshare has high toughness and improves the hardness and wear resistance of the wear service part of the ploughshare tip; TiC and Al generated in situ by combustion synthesis reaction 2 O 3 The microhardness of the added nickel-based WC particles is significantly higher than that of the chromium carbides in the cladding material that play an anti-wear role. The volume fraction of hard ceramic particles is between 40 and 60%. The metal-ceramic alloy hardened layer has a dense structure, which makes it have excellent wear resistance.
[0076] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0077] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for manufacturing a cast bionic metal ceramic ploughshare, It is characterized in that The following steps are involved: Design a scale structure at the part where the plowshare touches the soil, and make a plowshare coated sand shell model with a scale structure; The water-based binder is mixed with the alloy powder to prepare an alloy powder paste, and the alloy powder paste is coated on the scale structure in the sand shell model of the plowshare coated sand and dried, wherein the alloy powder contains aluminum powder, titanium powder, chromium powder, Cr 2 O 3 powder, NiO powder, graphite powder and nickel-based tungsten carbide powder; The dried ploughshare coated sand shell model is assembled with the casting system and filled with quartz sand. The structural steel liquid is melted by the casting system to obtain a molten metal, which is then poured into the cavity of the ploughshare coated sand shell model. The molten metal triggers a combustion synthesis reaction to generate TiC and Al in situ on the flake structure. 2 O 3 At the same time, the metal melt infiltrates into the alloy particle layer, and physical and chemical reactions occur between the alloy powder particles to obtain a composite ploughshare casting; The composite ploughshare casting is heat treated to obtain a cast bionic metal ceramic ploughshare.
2. The method for manufacturing a cast bionic metal ceramic ploughshare according to claim 1, It is characterized in that The alloy powder contains 10wt% to 20wt% aluminum powder, 20wt% to 40wt% titanium powder, 5wt% to 20wt% chromium powder, and Cr 2 O 3 5wt% to 10wt% of nickel powder, 10wt% to 20wt% of NiO powder, 10wt% to 20wt% of graphite powder and 5wt% to 20wt% of nickel-based tungsten carbide particles, totaling 100%.
3. The method for manufacturing a cast bionic metal ceramic ploughshare according to claim 2, It is characterized in that The particle size of aluminum powder is 5μm~40μm, the particle size of titanium powder is 18μm~150μm, the particle size of chromium powder is 20μm~150μm, and the particle size of Cr 2 O 3 The powder particle size is 2μm to 25μm, the NiO powder particle size is 2μm to 25μm, the graphite powder particle size is 1.3μm to 20μm, and the nickel-based tungsten carbide particle size is 20μm to 200μm.
4. The method for manufacturing a cast bionic metal ceramic ploughshare according to claim 1, It is characterized in that The structural steel is one of ZG20CrNiMoRE, ZG25CrNiMoRE and ZG30CrNiMoRE, wherein the carbon content of ZG20CrNiMoRE structural steel is 0.18% to 0.22%, the carbon content of ZG25CrNiMoRE structural steel is 0.22% to 0.28%, and the carbon content of ZG30CrNiMoRE structural steel is 0.28% to 0.32%.
5. The method for manufacturing a cast bionic metal ceramic ploughshare according to claim 1, It is characterized in that The coating thickness of the alloy powder paste is 4 mm to 10 mm.
6. The method for manufacturing a cast bionic metal ceramic ploughshare according to claim 1, It is characterized in that The pouring temperature is 1570℃~1620℃.
7. The method for manufacturing a cast bionic metal ceramic ploughshare according to claim 1, It is characterized in that The heat treatment operation is: first keep the temperature at 930°C to 980°C for 2 hours to 6 hours, cool to room temperature, and then keep the temperature at 280°C to 340°C for 1 hour to 4 hours for tempering.
8. The method for manufacturing a cast bionic metal ceramic ploughshare according to claim 1, It is characterized in that In the alloy powder paste, the volume fraction of the water-based binder is 10% to 30%.
9. The method for manufacturing a cast bionic metal ceramic ploughshare according to claim 1, It is characterized in that The water-based adhesive is one of an arabic gum aqueous solution, a potato starch adhesive aqueous solution, and an ethylene-vinyl acetate copolymer emulsion adhesive. The mass concentration of the arabic gum aqueous solution is 1% to 10%, the mass concentration of the potato starch adhesive aqueous solution is 1% to 8%, and the mass concentration of the ethylene-vinyl acetate copolymer emulsion adhesive is 5% to 15%.
10. A cast bionic metal ceramic ploughshare made by the manufacturing method according to any one of claims 1 to 9, It is characterized in that The cast bionic metal ceramic ploughshare consists of a ploughshare base (1) and a metal ceramic coating (2) at a soil contacting portion.
